(untitled) (Journal of Philosophy Culture and Political Science, 2021)
In this article, the author defines the key features and approaches to understanding the phenomenon of power: in its variety of forms and types. Modern approaches and methods of power research are used and the key problems of the phenomenon of power in the context of philosophical analysis are determined, as well as issues of various levels of power are touched upon. There are a large number of opposite and incomparable concepts of power: three levels of power relations, individual as well as objective power, power as an influence, etc. The author believes that the best method for the phenomenon of power is to realize the integrity of these concepts of power - to analyze power as such, accepting the internal characteristics of this phenomenon, while reasoning about this, how power relations are realized in various social structures. However, not without exception, the internal characteristic features of power can equally determine the essence of the phenomenon of power, namely: the worldview area is an internal reflection of a moral and honest socio-political player who is trying to adequately implement power. This inner and practical view of power will shed light on many of the theoretical mysteries of power. This study of the phenomenon of power determines the differences in the judgments of those who have the ability to exercise power. Keywords: power, subordination, social theory, phenomenon of power, philosophy of power.